Application of the harmonic control arrays technique to single-phase stand-alone inverters - DOĞRUEL, MURAT (INST ENGINEERING TECHNOLOGY-IET, 2016)
This study proposes the adaption of the harmonic control array (HCA) technique to control a single-phase stand-alone inverter system. The HCA method is recently proposed as an efficient scheme to control the systems with periodic references or disturbances. The HCA appropriately adjusts the harmonic components of the control signal to obtain a zero steady-state error. Since the signals and parameters involved in this method are complex valued, a discrete time implementation is presented for applying the method through a digital platform. The design procedure of the controller parameters are also presented by details. To confirm the theoretical achievements, experimental results for the prototype system are presented in this study. The results demonstrate the effectiveness of the proposed control scheme.
Keywords: REPETITIVE CONTROL SCHEME; COMPENSATION; FRAME; DESIGN; OPTIMIZATION; TRANSIENT; FILTER